What can the EMU's peripheral countries learn from regional growth? - Karl Aiginger; Matthias Firgo; Peter Huber (WWWforEurope, 2013)
The experiences of 259 regions in 21 European countries with within country GDP per capita and labour productivity growth suggest that variables associated with pro-active, growth oriented strategies are consistently more important predictors of successful regional development than variables related to austerity for a range of measures of successful development. Since regions are the only historical examples of restructuring in currency unions, we therefore also argue for a more growth oriented strategy to solve the problems of the European periphery and outline some features of such a strategy.
Keywords: O52; R11; R58; 330; Convergence; within-country growth; peripheral countries